What's "quickest and easiest?": parental decision making about school trip mode - Faulkner Guy EJ; Richichi Vanessa; Buliung Ronald N; Fusco Caroline; Moola Fiona (BMC, 2010)
Abstract Background The potential benefits of active school travel (AST) are widely recognized, yet there is consistent evidence of a systematic decline in the use of active modes of transportation to school since the middle part of the 20th century. This study explored parental accounts of the school travel mode choice decision-making process. Methods Thirty-seven parents of children (17 who walked; 20 who were driven) from four elementary schools in Toronto, Canada participated in semi-structured interviews. The schools varied with respect to walkability of the built environment and socio-economic status. Thematic analysis of interview transcripts identified a two-stage decision-making process. Results An initial decision concerned the issue of escorting or chauffeuring a child to/from school. This decision appeared to be primarily influenced by concerns about traffic, the child's personal safety, and the child's maturity and cognitive ability regarding navigating his/her way to/from school safely. Following the escort decision, parents considered mode choice, typically selecting what they perceived to be the easiest and most convenient way to travel. The ascription of convenience to the various modes of transportation was influenced by perceptions of travel time and/or distance to/from school. Convenience became a particularly salient theme for parents who found it necessary to complete multi-activity trip chains. Conclusions The school travel mode choice decision process is complex. Future research and practice should continue to address safety concerns that are typically the focus of active school transport initiatives while addressing more explicitly the behavioural cost of competing mode choices.